COOPERATION BETWEEN RUSSIA AND BAHRAIN IN THE FIELD OF REGIONAL SECURITY - A. Khaled Mohamed Ali (Vestnik MGIMO-Universiteta, 2017)
The article examines the current state of and prospects for cooperation of the Russian-Bahraini relationship in the context of the formation of a regional security system. The author analyzes the bilateral agenda between Moscow and Manama in the broad context of the legacy of the USSR in the region, the wide-ranging course of the Russian Federation towards the Middle East in general and the states of the Persian Gulf in particular. Also, the study takes into account the factor of other extra-regional presence in this subsystem, special attention in this context is paid to the role of the United States. As a result of the analysis, the author formulated his own characteristic of the general trends of Russian policy towards the countries of the Persian Gulf. At the same time, relations with Bahrain were considered in the framework of several “baskets” - the most relevant problems for both states, whose influence could be extrapolated from the bilateral agenda to regional and subregional security issues. To such “baskets” the author included problems: Arab-Persian contradictions, terrorism and extremism, Shia-Sunni confrontation, interstate relations in the format of the Cooperation Council for the Arab States of the Gulf. The subject of the study was concentrated on the compatibility of Russian and Bahraini positions on these issues in the context of the formation of a regional security system.